The Effect of the Application of Contextual Teaching and Learning (CTL) on the Students’ Vocabulary Mastery at Grade Seven of SMP Gajah Mada Bandar Lampung in Academic Year 2013-2014 - Dewi Marsela (Bandar Lampung University (UBL), 2014)
The objective of this research is to find out the effect of the application of Contextual Teaching and Learning (CTL) on the students’ vocabulary mastery at grade seven of SMP Gajah Mada Bandar Lampung in academic year 2013-2014. Contextual Teaching and Learning (CTL) was applied to increase the students’ vocabulary mastery which was used as one of visual method to help the students to master vocabulary and make them interested in learning English. The data was collected by in cooperatingtwo pre-tests and two post-tests in experimental group and control group. Treatment using Contextual Teaching and Learning (CTL) was administered in experimental group, while control group received by other technique without any special treatment. The data analysis was attempted using t-Test for two group design. The result indicated that p-value 1% = 2.68, 5% = 2.00, and t-value = 3.77. It means that p-value is smaller than t-value. Therefore, hypothesis testing showed that null hypothesis (Ho) was rejected and alternative hypothesis (Ha) was accepted. The writer concluded that the application of Contextual Teaching and Learning (CTL) was more effective than other technique without any special treatment.It can be concluded that teaching vocabulary through Contextual Teaching Learning (CTL) is quite success. It can be seen on the result of calculated the students’ score. Vocabulary scores that the students who learn vocabulary through Contextual Teaching Learning has a significant difference. It means that there is a significant influence of using Contextual Teaching Learning in teaching vocabulary.